Using Drama Activities As A Catalyst In Improving Communicative Confidence: A Case Study - Mohd. Nawi, Abdullah; Mustaffa Ng, Ady Mukhtarrudin (2010)
This case study is about the use of drama activities as a catalyst in improving communicative confidence. The purpose of this study is to investigate the efficacy of drama activities in improving students’ confidence in communicating using English, identify students’ views on the use of drama activities as a communicative confidence-building tool, and consequently suggest how these activities can be incorporated in English language teaching. For this purpose, a workshop was organised and communicative drama activities were carried out with the participants of the programme, made up of 24 students from Universiti Teknologi Malaysia. Data for the study was obtained from these participants via feedback forms and questionnaires that were distributed to them. The data was then analysed qualitatively and quantitatively. The research findings show that a majority of the participants reacted positively to the communicative drama activities and also agree with the use of drama activities in improving communicative confidence. At the end of the study, the suitability of drama activities as a tool for communicative confidence-building is determined. Besides that, suggestions for effective incorporation of communicative drama activities in English language teaching are also given.